Culture of Eisenia fetida (Annelida, Lumbricidae) on puffed rice scrap in outdoors and laboratory conditions - Schuldt, Miguel (2005)
Industrial puffed rice scrap increases the carbon/nitrogen ratio in carbon-poor biodegradable organic matter, such as broiler chicken beddings (C/N= 14.6) (droppings + sunflower husks), optimizing the composting process. In Eisenia fetida field experiences (bimonthly sampling) done on cultures managed through self-inoculation (addition of 8-16% scrap to the chicken bedding), the substrate was accepted. Population increase and cocoon production, measured 127 days after the start, were not significantly different from control plots (broiler chicken bedding). Population size expanded with a nominal (nd) and effective (ed) increase of 2.69 and 3.51 times respectively compared to the initial numbers. The carrying capacity of the different organic matter mixtures approximates 30000 worms/bed (2m²) (w/B). The reproductive potential ( R ) showed fluctuations (between 1000 and 10800 w/B) which agree with the dynamics of a population under this management strategy. Humus production was approximately 35 tons from an original 63.9 tons. In laboratory cultures (weekly weight control) with pure scrap, as worm substratum-feed, the following results, compared to home waste compost and rabbit manure (control), were recorded: more sexually mature animals; higher cocoon-per-animal production; average weight (at 17 weeks) a 47% higher than the weight obtained when using other diets.